Tunable white emission from scintillated zinc borosilicate doped with dysprosium oxide and incorporated with bio-silica from rice husk - Abdul Wahab, Rabiatul Adawiyah; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Mohamed Kamari, Halimah; Sarmani, Abdul Rahman; Zhi, Wei Loh; Wei, Mun Cheong; Sawao, Honda; Yuji, Iwamoto (Elsevier GmbH, 2022)
A series of zinc borosilicate glass doped with dysprosium oxide (Dy-ZBS) has been successfully fabricated through the conventional melt-quench technique with the incorporation of bio-silica source from rice husk ash. The physical, structural, luminescence, and optical properties of the fabricated glass have been studied utilizing the bulk density, x-ray diffraction pattern, photoluminescence emission spectra, chromaticity coordinates, absorption spectra, and optical band gap. The bulk density improved from 3.468 gcm− 3 to 3.635 gcm− 3 as the dopant concentration increased due to the compactness of the network structure. The amorphous nature of the glass has been justified by using an X-ray diffraction pattern. Whereas the photoluminescence emission spectra have been confirmed the presence of blue and yellow colors and were intensified as the Dy3+ increases. The CCT values from chromaticity diagram of the best white light-reaching coordinates are (0.3028, 0.3334) and classified as cool white. The optical absorbance was found to be enhanced as the Dy2O3 raised from 0 wt% to 3 wt%. Meanwhile, both the direct and indirect optical band gaps were decreased consecutively. Thus, this fabricated glass is suggested to be future solid-state light materials as a white light-emitting diode (WLED) light source.